Prática de autocuidado de pacientes com hipertensão arterial na atenção primária de saúde - Cláudia Rayanna Silva Mendes; Maira Di Ciero Miranda; Francisca Elisângela Teixeira Lima; Eva Anny Wélly de Souza Brito; Igor de Freitas; Érica Oliveira Matias (Universidade Federal do Ceará, 2016)
Objective: to evaluate the practice of self-care performed by patients with systemic arterial hypertension in primary health care. Methods: this is a descriptive and cross-sectional study, conducted with 92 individuals with arterial hypertension in a primary care unit. The data collection occurred through script and data analyzed using descriptive statistics (frequency, mean and standard deviation) and through the understanding of the adaption between capacity and self-care demand. Results: it was identified as a practice of self-care: adequate water intake, salt intake and restricted coffee, satisfactory sleep period, abstinence from smoking and alcoholism, continuing pharmacological treatment and attending medical appointments. As the demands: inadequate feeding, sedentary lifestyle, had no leisure activities, self-reported stress, and limited knowledge. Conclusion: although patients performed treatment a few years ago, still showed up self-care deficits, highlighting the need for nurses to advise and sensitize about the importance of self-care practice.